The Characteristics of the Sundanese Language ''Aing Tangerang'': Diversity and Loss of Cultural Identity - Ijum Setiawan (IRDH International Journal of Social Sciences & Humanities, 2025)
In recent decades, a worrying phenomenon has occurred is the declining using of the Sundanese language among the younger generation. This research focussed on various social, cultural, and psychological aspects that affect the use of Sundanese in Tangerang, with the aim of providing insights that can help communities, governments, and educational institutions in formulating more effective conservation strategies. This study used a qualitative approach with in-depth interview methods and participatory observation. The results showed that the use of Sundanese in Tangerang continues to live in certain families and communities, although not as much as in the past. People in Tangerang still maintain this language in their daily conversations, although it is starting to be rarely found in public spaces. One of the characteristics of the Sundanese language that still survives in Tangerang is the expression "aing Tangerang" . ‘’Aing Tangerang" not only reflects pride in personal identity, but also becomes a symbol of a community that is deeply rooted in local history and culture. Some of the factors that caused the decline in the use of Sundanese in Tangerang include Globalization and Modernization, Social Displacement and Urbanization, and also The Influence of Technology and Social Media. The Impact of the Loss of Sundanese Language on Cultural Identity are Erosion of Cultural Identityand The Young Generation Alienated from Cultural Roots. To preserve the Sundanese language in Tangerang, several conservation efforts can be made Sundanese Language Teaching in Schools, Increasing Public Awareness, and Utilization of Social Media and Technology